Patriarchal Oppression and Women Empowerment in Chimamanda Ngozi Adichie’s Purple Hibiscus - Tifanny Astrick (Vivid: Journal of Language and Literature, 2018)
This study examines how Chimamanda Ngozi Adichie's Purple Hibiscus interrogates the oppressions of women in the Nigerian patriarchal society and how women empower each other lead them to women empowerment. The study shows how the oppressions of women is represented through female characters which perpetually put women in disadvantaged positions as portrayed in Purple Hibiscus. One of the most despicable oppression among the so well-known cultural practices in Nigeria is the patriarchal oppression. However, as the events unfold, efforts will be made in order to reveal of how African women are rated based on the good and real women as represented by Beatrice and Ifeoma. I argue that Adichie's approach to subvert patriarchal oppression describes that despite the struggle and pain, women assert themselves in the world of patriarchy through education and sisterhood. Adichie’s novel suggests women empowerment through social transformation confronted by women. The title of the novel, "Purple Hibiscus" may refer to a particular type of flower, but it also emphasizes the triumph of the innovative suggesting that the unusual is not necessarily bad as it looks which aims to women empowerment.